Peran Stakeholders Dalam Pengelolaan Dan Akuntabilitas Lingkungan Pada Mal Ratu Indah Makassar - Salam, Nun Fadilah (Bongaya Journal of Research in Accounting (BJRA), 2019)
This study aimed to investigate the role of stakeholders in environmental accountability and management practices on the Ratu Indah Makassar Mall. This study used a phenomenological approach in which the researcher collected data using participant observation to find out the essential phenomena of participants in their life experiences. The study began from October 2018 to March 2019. The data collection method used interviews with HRD Staff, Operational Section Head and Greenship Manager about the role of stakeholders in environmental accountability and management, observation of stakeholders involvement in environmental accountability and management and documentation. The data analysis method used the analysis of Miles and Huberman, namely data collection, data reduction, data presentation, drawing conclusions and verification. The results of the study showed that the role and engagement of stakeholders in environmental accountability and management, both in the form of participation, cooperation, supervision and inspection can strengthen relations between companies and stakeholders, create customer satisfaction and comfort, improve environmental performance and contribute to the development and business sustainable.